Agenesis of the long head of the biceps brachii tendon: ignored variations of the anatomy and the next tendon to disappear?. Issue 5 (5th May 2020) - Traverso, Aurélien; Piasecki, Krzysztof; Gallusser, Nicolas; Farron, Alain
Abstract : Bilateral agenesis of the long head of the biceps brachial tendon (LHB) is a very rare variation of the anatomy. We report a case of an 18-year-old man with bilateral agenesis of the long head of the biceps brachii tendon. We present initial findings, radiographical examinations and the follow-up of an unusual entity. Diagnosis of agenesis of the LHB can be challenging especially in cases of traumatic shoulder pain. It is not a very known entity because of its rareness. However, it could be associated with other congenital anomalies. The absence of the LHB is easily ignored in the diagnostic process. Clinical examination should be a pitfall, radiological examination is helpful to confirm the suspicion of LHB absence. MRI is often the first choice, although ultrasonography is cheaper and much easier to access and it is an excellent tool to visualise this anatomic variation with empty or shallow intertubercular groove.